Evolution of the True Contact Area of Laser Textured Tungsten Under Dry Sliding Conditions - Lechthaler, Björn; Ochs, Georg; Mücklich, Frank; Dienwiebel, Martin (Frontiers in Mechanical Engineering, 2019)
Despite the great importance of the real contact area, it is a parameter which, depending on the tribological system, is difficult or impossible to obtain experimentally. In this work, a combination of methods was used to estimate the development of the real contact surface, and the results were compared with the friction coefficient course. The measurements were carried out with a home-built in situ tribometer, which records a 3D image of the surface after each individual friction cycle. A tungsten sample was treated by laser interference with a line-like pattern to produce a deterministic surface. This allowed for more precise tracking of the real contact area when combined with the use of an inert corundum sphere as a counter-body. The real contact area was calculated numerically from the height information obtained using a contact application. Finally, the true contact surface was compared with the parallel-recorded friction values. After a short running-in phase, the friction behavior and the real contact surface showed comparable courses. This indicates that the changes in the real contact area could explain the friction behavior of the laser-patterned sample, and the methodology was proven to be suitable for experimentally estimating the real contact area.